2021
DOI: 10.1021/acsami.1c19906
|View full text |Cite
|
Sign up to set email alerts
|

Layer-by-Layer Growth of AA-Stacking MoS2 for Tunable Broadband Phototransistors

Abstract: The stacking configuration has been considered as an important additional degree of freedom to tune the physical property of layered materials, such as superconductivity and interlayer excitons. However, the facile growth of highly uniform stacking configuration is still a challenge. Herein, the AA-stacking MoS 2 domains with a ratio up to 99.5% has been grown by using the modified chemical vapor deposition through introducing NaCl molecules in the confined space. By tuning the growth time, MoS 2 domains would… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 61 publications
1
34
0
Order By: Relevance
“…SARS-CoV-2 is a positive-sense single-stranded RNA virus of about 30000 base length. In recent years, some studies have studied the charge transport in nanomaterials [5] , [6] and the electrical properties of cytosine hydroxymethylated (Chm) DNA sequences [7] . A recent article found that single-molecule conductance techniques can be used to extract biologically relevant information from short RNA oligonucleotides by construct RNA:DNA hybrids [8] .…”
Section: Introductionmentioning
confidence: 99%
“…SARS-CoV-2 is a positive-sense single-stranded RNA virus of about 30000 base length. In recent years, some studies have studied the charge transport in nanomaterials [5] , [6] and the electrical properties of cytosine hydroxymethylated (Chm) DNA sequences [7] . A recent article found that single-molecule conductance techniques can be used to extract biologically relevant information from short RNA oligonucleotides by construct RNA:DNA hybrids [8] .…”
Section: Introductionmentioning
confidence: 99%
“…There are two typical vibration modes located at 384.69 and 404.18 cm –1 corresponding to the in-plane vibration mode (E 2g ) and out-of-plane vibration mode (A 1g ), respectively. The distance between the A 1g and E 2g is about 19.49 cm –1 , which further indicates its monolayer structure. , The typical photoluminescence band is located at about 668 nm. To fabricate the MoS 2 -based ion-gel phototransistor, the CVD-grown MoS 2 flake has been transferred to the precleaned sapphire substrate.…”
Section: Resultsmentioning
confidence: 84%
“…Therefore, the ion-gel does not obviously affect the electrical and photoelectrical properties of MoS 2 . The carrier mobility could be calculated by the equation , where C ox is the capacitance of the ion-gel membrane, L and W are the channel length and channel width, respectively, and I d and V d are separately the drain current and voltage. To estimate the C ox value of the ion-gel film, the frequency-dependent capacitance has been studied as shown in Figure S5, and the capacitance is about 10.5 μF/cm 2 at 0.1 Hz.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Transition-metal dichalcogenides have gained a lot of popularity in recent years mainly because of the advantages they provide in terms of their usage in field-effect transistors (FETs), photodetectors, photodiodes, solar cells, and phototransistors . The layers of two-dimensional (2D) materials can be ultrathin, and the band gap can be tuned according to the thickness of the layers of the material from monolayer to multilayer. MoS 2 is a very promising 2D material because of its outstanding performance in terms of carrier mobility, tunability of excitonic effects, and high current density of monolayer .…”
Section: Introductionmentioning
confidence: 99%